Cobertura comestível à base de PVA para conservação de tomates - Candéo, Manuella (2020)
This study aimed to develop an edible cover based on polyvinyl alcohol (PVA), accompanied by physicochemical characterizations, to preserve commercial quality, improve storage capacity, and increase the shelf life of tomatoes (Solanum lycopersicum). The methodology of this work was divided into two distinct stages. The first consisted of preparing five toppings, four based on PVA solution additive with essential oils of thyme, oregano, rosemary, clove and one of them without additives. These solutions were used to cover tomatoes that were still green, with monitoring of ripening carried out over a period of thirty days through chemical physical analyses, in order to compare the characteristics of the fruits in the face of the treatments, it was possible to observe that the fruits treated with essential oil presented delayed in their maturation. In the second stage, mature tomatoes (red) were used, with three treatments, besides the control: PVA solution, silk paper covered with PVA, only silk paper, with results analyzed during nineteen days, and physicochemical analyses were performed. The tomatoes covered with PVA-based solution remained fit for consumption until the end of the study time, while in the other toppings the tomatoes lasted only until the eleventh day. The edible coverage of PVA showed a viable alternative in order to delay the senescence of tomato fruits, and when added essential oil bring benefits in conservation and delay in ripening.